A CONTRASTIVE ANALYSIS OF ENGLISH AND ARABIC TENSES - Khalida Fahmi Tanjung; Zainuddin (State University of Medan, 2015)
The study deals with the similarities and differences of Tenses in English andArabic Tenses. The application to the language teaching and learning process. Inthis study the researcher focuses on the three main tenses of both languagesnamely simple Present Tense, simple Past Tense, and Future Tense, that isdescribing the verb systems of both languages based on to each tense. The datathat support this study are obtained by applying a documentary technique thatselected by reading some references related to the subject matters. The data areanalyzed by using the theory of Contrastive Analysis to found out the similaritiesand differences of tenses in English and Arabic. The findings show some aspectsof tenses in English are similar to those in Arabic. The differences are bothEnglish and Arabic has different number of pronoun. English consists of sevenpronouns while Arabic pronouns are fourteen which influence the verb formation.